Frontal Brain Asymmetry in Restrained Eaters. - Silva, Jaime R.; Pizzagalli, Diego A.; Larson, Christine L. (Journal of Abnormal Psychology, 2002)
It is well known that the eating patterns that restrain chronic dieters (restrained eaters) can be disinhibited by anxiety, which in turn has been associated with relative right frontal brain activity in independent electroencephalographic (EEG) studies. Combining these two lines of evidence, the authors tested the hypothesis that chronic eating is associated with relative right frontal asymmetry. Resting anterior brain asymmetry and self-reported measures of anxiety and depression were collected in 23 restrained and 32 unrestrained eaters. As hypothesized, groups differed in tonic frontal activity, with restrained eaters showing more relative right frontal activity. Furthermore, relative right frontal activity was associated with greater self-reported restraint. Right-sided prefrontal asymmetry may thus represent a diathesis associated with increased vulnerability toward restrained eating. Reprinted by permission of the publisher.